Internal audit quality and its association with financial distress: An Australian context - Chang, Kum Hong (Vincent) (Curtin University, 2017)
This study examined the impact of internal audit functions and those with internal audit quality attributes on financial distress computed by Altman and Zmijewski models. 865 ASX firms from 2012 to 2014, and 43 firms from 2013 to 2014 were used to examine the impact of internal audit functions and internal audit quality attributes respectively. Mixed results in terms of significant and directionality were found and institutional theory may explain their impacts on financial distress.